Taking politics seriously. Evaluating Real-world laboratories (RwLs) as drivers of urban transformations - Kampfmann, Teresa (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
Cities are seen as central to achieving the UN Sustainable Development Goals. It is argued that policy agendas are easier to implement at the local level than at the national or supranational level. The potential of cities is increasingly recognized at a time when impacts of the climate crisis are becoming more tangible and global efforts to proactively address the causes have been insufficient. Accordingly, there has been a growing debate on how to initiate urban transformations. In Germany, Real-world laboratories (RwLs) have attracted a considerable amount of attention in this context. RwLs, in which scientific actors work together with non-scientific actors to develop and test sustainability solutions, are seen both in the funding landscape and in the scientific literature as an opportunity to initiate sustainability transformations in urban areas. While the potential of RwLs in the context of urban transformations has been discussed and early experiences have been accumulated, a systematic examination of RwLs as drivers of political urban transformations is missing. Building on RwLs that involve actors from city administrations, a political turn in sustainability science, and literature that describes urban transformations as inherently political, this dissertation addresses the evaluation of RwLs in the context of political urban transformations. Through the inclusion of four research articles, the cumulative dissertation aims to answer the following question: How can we evaluate Real-world laboratories (RwLs) as drivers of urban transformations? The dissertation adopts a qualitative research approach. In the four research articles included, I have applied empirical, conceptual and reflective approaches to evaluation. The four articles are based on a shared epistemological understanding. They use natural, pre-existing data to evaluate RwLs. The initial question, ‘How can we evaluate RwLs as drivers of urban transformations?’ is answered in three steps that focus on different components of the initial question and bring together the findings of the included research articles. First, the role of the evaluator is addressed. The combination of different bodies of knowledge is transferred from the level of the transdisciplinary working group to the individual level of the transdisciplinary researcher conducting the evaluation. I discuss how transdisciplinary researchers can combine and make transparent the knowledge they bring from their academic affiliation and the experimental knowledge they gain from the practical implementation of the RwLs and the associated exchanges with the other actors involved in the RwLs (articles #1 and #4). Second, I approach what is being evaluated. Based on my articles #2 and #3, I assess how RwLs are connected to urban transformations. I introduce RwLs as governance networks, and as changers of urban governing systems. Thus, I perceive RwLs in terms of the process as well as the outcome understanding of urban transformations (articles #2 and #3). Third, I elaborate and describe conceptual counterparts to the practical evaluation of RwLs. These can serve as guiding principles for the development of RwL evaluation, particularly in the context of urban transformations. They have been developed based on the evaluations I have designed and conducted in the case-based articles #2, #3 and #4. In this way, the contribution of the dissertation lies in three areas. First, I hope to contribute to a discourse on RwLs that pays attention to the different bodies of knowledge of transdisciplinary researchers, and that considers existing, natural documents in the evaluation of RwLs. I also aim to contribute to a stronger connection between RwLs and governance approaches. The view of RwLs as contexts for learning and trialing practical sustainability solutions can be expanded to include governance perspectives. Finally, I attempt to inform practical evaluations. The proposed conceptual counterparts function as design choices for the conceptualization of empirical evaluations.
Keywords: Real-world Laboratory; Urban Transformation; Societal Impact; Political Impact; Sustainability; 300 Sozialwissenschaften